Chronic postoperative inguinal pain after open inguinal hernioplasty: prevalence and clinical characteristics in a Mexican secondary care hospital - Flores, Joseline Sanchez; Quiñones, Uriel Figueroa; Vazquez, Maria Urbelina Fernandez (International Surgery Journal, 2026)
Background: Chronic postoperative inguinal pain, also known as inguinodynia, is one of the most clinically relevant complications following open inguinal hernia repair and may significantly impair quality of life. This study aimed to determine the prevalence and clinical characteristics of chronic postoperative inguinal pain in patients undergoing open inguinal hernioplasty at a secondary care hospital in Mexico. Methods: A prospective, descriptive, cross-sectional, single-center study was conducted in adult patients who underwent open inguinal hernioplasty at Hospital General de Zona No. 20, Puebla, Mexico, between 2024 and 2025. A total of 94 patients were included through simple random probabilistic sampling. Data were obtained from clinical records and follow-up interviews performed either by telephone or in person using a standardized questionnaire. Variables included age, sex, body mass index, presence and intensity of inguinal pain and use of non-steroidal anti-inflammatory drugs. Results: The prevalence of chronic postoperative inguinal pain was 17% (16/94), corresponding to approximately one in six patients. Most symptomatic patients were male and between 35 and 54 years of age. Pain intensity was predominantly mild to moderate; however, a small subgroup reported severe to very severe pain. Compared with previously published data, our prevalence was slightly lower than the 24.8% reported in open repair cohorts. Conclusions: Inguinodynia remains a frequent complication after open inguinal hernioplasty. Although most patients presented mild to moderate symptoms, severe pain requiring specialized management was identified in a minority. Standardized postoperative surveillance protocols may improve early recognition and treatment.